Monument of Sir Andrew Judd, Knight Sheriff in 1544 and Mayor 1551 - Stow, James; Fisher (Tufts Archival Research Center, 2008)
Erected in the choir of the Church of St. Helen, Bishopsgate. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.